Prepared σ-MnO2 thin films by chemical bath deposition methods and study of its optical and microstructure properties - Astinchap, Bandar; Moradian, Rostam; Namdari, Tahereh; Jurečka, Stanislav; Ţălu, Ştefan (Optical and quantum electronics, 2019)
In this work, σ-MnO 2 thin films deposited by chemical bath deposition method at three concentration of solution. The influence of concentration on thickness, micromorphology and optical parameters were investigated by XRD, SEM, UV–Vis spectrophotometer, atomic force microscopic and multifractal analyses. The optical band gap of thin films is decreased with increase in concentration. The optical parameters: refractive index and real part of dielectric constant are increased with increase in concentration, but decrease in extinction coefficient and imaginary parts of dielectric constant are observed. The micromorphology and roughness of layers surface are changed as function of concentration. The studied samples have multifractal properties and can be included in computer algorithms useful for graphical representation of 3-D microtexture surfaces of σ-MnO 2 thin films.